Experiential learning for entrepreneurship : theoretical and practical perspectives on enterprise education - Hyams-Ssekasi, Denis; Caldwell, Elizabeth F. (Palgrave Macmillan, 2018)
This topical new book provides an illuminating overview of enterprise education, and poses the question as to whether current establishments have adequate systems in place to prepare students for the world of work. Addressing the increasing need for graduates with practical skills and expertise in the labour market, this collection of insightful chapters analyses the opportunities that are available for aspiring entrepreneurs to develop enterprise skills and experience key aspects of starting and running a business, whilst in a supported environment such as an educational program or incubator scheme. With comprehensive discussion of higher education initiatives and empirical examples of experiential learning in the workplace, this book is an important and timely read for those researching business enterprise, entrepreneurship and higher education more generally.- Resumé vydavatel
Keywords: podnikatelská výchova; podnikání; vysokoškolské studium; entrepreneurship education; business; college study; elektronické knihy; monografie; electronic books; monographs